Communication Resilience among Chronic Illness Patients: A Phenomenological Study of Hepatitis B Survivors Facing Social Stigma - Aphrodid Aisyah; Adethya Napitupulu; Rafi Dwiko Alif Prananda (Yayasan Citra Dharma Cindekia, 2026)
This study aims to explore the communication resilience demonstrated by Hepatitis B survivors after overcoming the critical stages of their illness, particularly when dealing with social stigma. Chronic diseases not only affect physical health but also generate psychological and social challenges due to prejudice and limited public understanding. Employing a qualitative phenomenological approach, this research investigates the communication experiences of two female Hepatitis B survivors who have encountered stigmatizing attitudes within their social environment. Buzzanell’s (2010) Communication Resilience Theory is used as the analytical framework to examine how individuals reconstruct their identities, maintain social relationships, and create new meanings in response to adversity. The findings reveal that both participants experienced substantial communication challenges, including social exclusion, negative remarks, and misunderstandings arising from inadequate health literacy among community members. Despite these difficulties, they exhibited communication resilience through several strategies, such as controlling the disclosure of personal information, relying on family support, and developing more constructive self-narratives. These findings suggest that resilience extends beyond mere survival; it represents an active communicative process through which survivors adapt, recover, and continue to build meaningful lives despite experiencing social stigma.